2007
DOI: 10.2113/gscanmin.45.3.631
|View full text |Cite
|
Sign up to set email alerts
|

Chromian Spinel Composition and the Platinum-Group Minerals of the Pge-Rich Loma Peguera Chromitites, Loma Caribe Peridotite, Dominican Republic

Abstract: The Loma Peguera chromitites are located in the central part of Loma Caribe peridotite in the Cordillera Central of Dominican Republic. The chromitite bodies are hosted in typical mantle peridotites, have small size (less than a few meters across) and show massive textures. Primary chromite composition is Cr-rich (0.74 < Cr# < 0.78) and exhibits systematically high Ti (average value: 0.84 wt% TiO 2) and Fe 3+ (average value: 7.82 wt% Fe 2 O 3). The total PGE concentrations vary from 1.82 to 2.04 ppm, and show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(51 citation statements)
references
References 46 publications
2
43
0
6
Order By: Relevance
“…On the basis of their textural relationships, occurrence and composition, the PGM have been divided into (1) primary, formed in the magmatic stage, before and during the precipitation of chromite and (2) secondary, formed by the alteration of primary PGM at a relatively low temperature [2][3][4][5][6][7][8][9][10][11][12]. Paragenetic considerations indicate that in the Cedrolina chromitite only irarsite and laurite could represent relicts of the original igneous assemblage [54][55][56][57][58][59].…”
Section: The Accessory Minerals In the Cedrolina Chromitite And Theirmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of their textural relationships, occurrence and composition, the PGM have been divided into (1) primary, formed in the magmatic stage, before and during the precipitation of chromite and (2) secondary, formed by the alteration of primary PGM at a relatively low temperature [2][3][4][5][6][7][8][9][10][11][12]. Paragenetic considerations indicate that in the Cedrolina chromitite only irarsite and laurite could represent relicts of the original igneous assemblage [54][55][56][57][58][59].…”
Section: The Accessory Minerals In the Cedrolina Chromitite And Theirmentioning
confidence: 99%
“…The platinum group minerals (PGM), with few exceptions, are grouped among accessory phases, being rare and occurring as tiny particles dispersed in their host rocks. Recent investigations have shown that the primary/magmatic PGM may be altered to secondary PGM during metamorphism, as well as weathering and lateritization [2][3][4][5][6][7][8][9][10][11][12]. It has also been demonstrated that hydrothermal solutions and metamorphic fluids are capable of introducing incompatible elements in the alteration system of a chromitite, giving rise to the formation of exotic accessory minerals, such as monazite, galena, bismuthinite, and antimony that normally do not occur in unaltered chromitites [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…These authors have shown that secondary processes can cryptically modify the composition of primary PGM, which leads to the formation of new PGM phases. Alloys and oxides rich in Ru, Os and Ir are the most common secondary PGM encountered in podiform chromitites (e.g., Garuti & Zaccarini 1997, Ahmed & Arai 2003, Gervilla et al 2005, Proenza et al 2007, 2008.…”
Section: Previous Work On the Pgm Of Milia Chromititesmentioning
confidence: 99%
“…1B). Draper et al (1996) suggested that the Loma Caribe peridotite, a serpentinized harzburgite with minor dunites, lherzolites and pyroxenites forming part of a dismembered ophiolite complex (Lewis et al, 2006;Proenza et al, 2007), was tectonically emplaced over the Maimón Formation during the late Albian along a northward thrust; obduction resulted in deformation and metamorphism of the Maimón Formation, particularly in the Ozama shear zone. The Loma Caribe peridotite belt is separated from the Maimón Formation at their southern contact by the Peralvillo Sur Formation, a thin sequence of arc-related volcanic and volcanosedimentary rocks of Late Cretaceous (?)…”
Section: Accepted M Manuscriptmentioning
confidence: 99%